Digital Transformation of Import Logistics for Operational Efficiency: Case-Based Evidence from the Plastics Industry - Fajar Indra Kurniawan; Firdaus Alamsjah (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
This study aims to explore the use of digital systems to reduce import process costs, increase the percentage of national direct deliveries from ports to consumers, and analyze the impact of proposed improvement measures. The research employs a single case study approach with data collected through observation, document analysis, and quantitative data collection from one of the biggest plastic resin distribution companies in Indonesia. The data were analyzed using the CIMO (Context-Intervention-Mechanism-Outcome) logic to understand the context and impact of the interventions implemented. The findings reveal that the application of digital technologies such as the Internet of Things (IoT), Blockchain, and cloud-based management systems with real-time container tracking digital applications can optimize supply chain processes and sustainability. There was a notable reduction in the national average container storage costs at ports from 2.4/Ton to 1.8/Ton and an increase in the average percentage of national direct deliveries from ports to consumers from 17.3% to 22.0% before and after the implementation of the container tracking system. These results confirm that adopting digital technologies in plastic resin distribution companies not only improves operational efficiency, provides a competitive advantage in the market but also reduces carbon emission by using single trip directly to customers. Companies are advised to enhance employee training related to new technologies and adopt integrated systems within supply chain processes. Furthermore, continuous innovation using technologies such as artificial intelligence is essential for maintaining industry competitiveness and sustainability.